2021
DOI: 10.3390/agronomy11081496
|View full text |Cite
|
Sign up to set email alerts
|

The Survival and Parasitism Rate of Tamarixia radiata (Hymenoptera: Eulophidae) on Its Host Exposed to Beauveriabassiana (Ascomycota: Hypocreales)

Abstract: The effect of the entomopathogenic fungus Beauveria bassiana (BB-12) on the biological characteristics of Tamarixia radiata parasitizing Diaphorina citri was studied under laboratory conditions. Twenty 3rd–5th instar nymphs were exposed to a single already-mated female parasitoid (1 day old) and removed after 24 h. Subsequently, the nymphs were sprayed at 1, 24 and 48 h post-exposure with 1 × 108 conidial mL−1 suspension. The percentage of parasitism recorded was 22%, 35% and 41% at 1, 24 and 48 h, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Trichogramma pretiosum [ 24 , 47 , 52 ] and E. formosa [ 29 , 38 , 40 , 51 ] were the most researched parasitoids, followed by A. colemani [ 23 , 30 , 32 , 35 , 46 ], C. flavipes [ 55 , 58 ], and Diaeretiella rapae [ 18 , 43 ]. In terms of microorganisms, B. bassiana [ 17 , 18 , 24 , 26 , 32 , 33 , 35 , 40 , 42 , 43 , 48 , 51 , 52 , 54 , 55 , 57 , 58 , 59 , 60 , 61 , 63 , 64 , 65 ] was the most studied fungus, followed by M. anisopliae [ 30 , 34 , 36 , 37 , 48 , 49 , 50 , 51 , 53 , 55 , 57 , <...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trichogramma pretiosum [ 24 , 47 , 52 ] and E. formosa [ 29 , 38 , 40 , 51 ] were the most researched parasitoids, followed by A. colemani [ 23 , 30 , 32 , 35 , 46 ], C. flavipes [ 55 , 58 ], and Diaeretiella rapae [ 18 , 43 ]. In terms of microorganisms, B. bassiana [ 17 , 18 , 24 , 26 , 32 , 33 , 35 , 40 , 42 , 43 , 48 , 51 , 52 , 54 , 55 , 57 , 58 , 59 , 60 , 61 , 63 , 64 , 65 ] was the most studied fungus, followed by M. anisopliae [ 30 , 34 , 36 , 37 , 48 , 49 , 50 , 51 , 53 , 55 , 57 , <...…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-eight out of forty-nine combinations of biocontrol agents were reported as compatible [ 18 , 19 , 20 , 22 , 24 , 25 , 26 , 29 , 32 , 34 , 35 , 36 , 37 , 39 , 41 , 43 , 44 , 45 , 47 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 62 , 63 , 64 , 65 ] ( Table 1 ). Six combinations were reported as incompatible [ 17 , 27 , 28 , 42 , 51 ], often due to a lower emergence rate caused either by bad timing, direct infection, or too high dosage. No answer about compatibility was given for the five remaining ones [ 30 , 38 , 54 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the survival of the immature stages of D. gelechiidivoris was reduced by fungal treatment of their host, interestingly in general the developmental time of the eclosed wasps was not affected by the fungal treatment. Similarly, Ramos Aguila et al [ 55 ] found that the developmental time of Tamarixia radiata Waterston (Hymenoptera: Eulophidae) reared on Beauveria bassiana infected Diaphorina citri Kuwayama (Hemiptera: Liviidae) was similar to the parasitoids being reared on healthy hosts.…”
Section: Discussionmentioning
confidence: 97%
“…This is because, their performance in the field depends significantly upon abiotic factors such as temperature, humidity, UV light and rainfall (De Castro et al, 2013;Kumar et al, 2017) and are influenced by biotic factors such as multi-trophic interactions with plants, arthropods and plant pathogens (Meyling & Eilenberg, 2007;Meyling & Hajek, 2009). However, given favourable ambient conditions they can act against a variety of arthropod pest and can ensure minimal risk for non-target organism including specialist parasitoids and generalist predators (Lacey et al, 2015;Ramos Aguila et al, 2021).…”
mentioning
confidence: 99%